Comparative Analysis of the Effects of Monovalent and Divalent Ions on Imported Biopolymer-Xanthan Gum and Locally Formulated Biopolymers-Gum Arabic and Terminalia Mantaly - Ezeh, Okechukwu; Ikiensikimama, Sunday Sunday; Akaranta, Onyewuchi (Creative Commons, 2021)
Aim: Polymer flooding is used for enhanced oil recovery. Only polymers that can withstand harsh environments work best. HPAM is mostly the polymer used for enhanced oil recovery because it is available and cheap, but it does not withstand high temperatures and high salinity reservoirs. Xanthan Gum withstands high temperatures and high salinity reservoirs, but it is expensive and plugs the reservoir. The aim of this study is to compare the salinity stability of gum Arabic and Terminalia Mantaly, a novel biopolymer, with commercial Xanthan gum. Original Research Article Ezeh et al.; JENRR, 9(2): 33-46, 2021; Article no.JENRR.78165 34 Study Design: Locally formulated biopolymers from gum Arabic exudates bought from Bauchi State in Nigeria and from Terminalia Mantaly exudates obtained from the University of Port Harcourt. The appropriate rheological tests were carried out at the laboratory. Place and Duration of Study: The laboratory experiments were carried out at the department of Petroleum Engineering, Covenant University, Ota in Ogun State of Nigeria between 2020 and 2021.
Journal of Energy Research and Reviews9(2): 33-46, 2021; Article no.JENRR.78165
Keywords: Gum Arabic; monovalent and divalent ions; polymer solutions rheology; stability; terminalia mantaly; xanthan gum; STEM; University of Port Harcourt